Smartphones addiction associated with academic achievement among dental students: A cross-sectional study (2021)
Purpose: The study sought to examine the association between dental students' smartphone addiction and academic achievement. Methods: Study participants were 374 dental students from the Universidad Cooperativa de Colombia school of dentistry. Smartphone addiction was assessed using the short version of the Smartphone Addiction Scale (SAS-SV), an instrument that was validated a priori using item response theory, information function test, and confirmatory factor analysis. Students' semester grade point average (GPA) served as a measure of academic performance. The association between SAS-SV scores and GPA was tested using generalized linear modeling adjusting for covariates. Results: The prevalence of smartphone addiction was low (4.8%) in this sample of dental students. Smartphone use was significantly and positively associated with GPA (b = 0.012; 95% confidence interval = 0.005-0.020; P = 0.001) while accounting for students' age and year of study. Conclusions: Smartphone usage was positively associated with dental students' academic performance. Importantly, a small number of students were identified as suffering from smartphone addiction. Future research should help clarify the mechanisms underlying this association, identify students at risk for smartphone addiction, and further elucidate the relevance of these findings in dental education.